Towards a More Sustainable and Responsible Architectural Training: Tactical Urbanism Lab in Quito; [Hacia Una Formación Arquitectónica Más Sostenible y Responsable: Laboratorios de Urbanismo Táctico en Quito] - Muñoz-Parra, C (Universidad Austral de Chile, 2024)
The University Social Responsibility (RSU) management model is compared to the learningservice methodology (ApS) in the Traveling Tactical Urbanism Labs (LIUTS) in Quito, to discuss and assess the community relationships established by educational institutions. Most often, interventions are part of university outreach models as external actions that have no bearing over the changes in the universities’ internal management and university curriculum. Through this analysis, the goal is to reflect on practices and processes, to avoid isolation and increase impacts on learning and society. The investigation proposal stems from the permanent social and spatial inequalities prevailing in Latin America, which prove the need to strongly implement RSU models in academic and professional training. Thus, this shows that RSU and ApS educate citizens committed to their environment, making a contribution from architecture to increased spatial awareness. © (2024), (Universidad Austral de Chile). All Rights Reserved.